Recent Topics in Steroid and Asthma: Beyond the 'Classic' Concept of Action - Yasuhiro Matsumura (Global Journal of Allergy - Peertechz Publications, 2015)
Glucocorticoid (GC)s exert anti-inflammatory effects via binding to the glucocorticoid receptor (GR) (NR3C1), targeted gene expression, and protein synthesis, which need hours before the onset of the action (transactivation). GCs also suppress inflammation by direct or indirect interaction with transcription factors, such as activator protein-1 (AP-1) and nuclear factor-κB (NF-κB) (transrepression). Recently, the non-genomic actions of GCs were discovered on recognition of its rapid onset of action within seconds to minutes. GCs target many cells and tissues, including immune and inflammatory cells, airway epithelium, and airway smooth muscle (ASM). Of these, ASM is involved in altered airway contractility. A recent study demonstrated that GCs not only suppress inflammation but also exert direct effects on ASM gene expression which influence ASM function. GC resistance in the treatment of bronchial asthma remains a considerable clinical problem. Genes and cellular inflammatory phenotypes of glucocorticoid-resistant (GC-R) asthma have been revealed. Inflammation-associated protein kinase signaling and transcription factors affect GC actions through modulating GR function. Involvement of chromatin modifications have also been reported. Infection, reduced Vitamin D (Vit D), smoking, and obesity are preventable risk factors in GC-R asthma. Some of these recently available results are presented in this review.